Autocrine and Paracrine Effects of Vascular Endothelial Cells Promote Cutaneous Wound Healing. (12th April 2021) - Lu, Yang; Yang, Yuhao; Xiao, Liling; Li, Shenghong; Liao, Xuan; Liu, Hongwei
Abstract : Background . When vascular endothelial cells are subjected to external stimuli, paracrine hormones and cytokines act on adjacent cells. The regulation of the biological behaviour of cells is closely related to the maintenance of organ function and the occurrence and development of disease. However, it is unclear whether vascular endothelial cells affect the biological behaviour of cells involved in wound repair through autocrine and paracrine mechanisms and ultimately play a role in wound healing. We aimed to verify the effect of the autocrine and paracrine functions of vascular endothelial cells on wound healing. Materials and Methods . ELISA was used to detect platelet-derived growth factor, basic fibroblast growth factor, epidermal growth factor, and vascular endothelial growth factor in human umbilical vascular endothelial cell-conditioned medium (HUVEC-CM). Different concentrations of HUVEC-CM were used to treat different stem cells. CCK-8 and scratch assays were used to detect the proliferation and migration ability of each cell. A full-thickness dorsal skin defect model was established in mice, and skin wound healing was observed after the local injection of HUVEC-CM, endothelial cell medium (ECM), or normal saline. H&E staining and immunofluorescence were used to observe the gross morphology of the wound tissue, the epithelial cell migration distance, and the expression of CD3 and CD31. Results . HUVEC-CM promotes the proliferation and migration of epidermal stem cells, skin fibroblasts, bone marrow mesenchymal stem cells, and HUVECs themselves. Furthermore, HUVEC-CM can promote angiogenesis in mouse skin wounds and granulation tissue formation and can accelerate wound surface epithelialization and collagen synthesis, thereby promoting wound healing. Conclusion . Our results clearly suggest that it is practicable and effective to promote wound healing with cytokines secreted by vascular endothelial cells in a mouse model.